Algebraic generalization strategies of number patterns used by pre-service elementary mathematics teachers - (:unkn) unknown (ELSEVIER SCIENCE BV, 2010)
This study investigates algebraic generalization strategies of 147 pre-service elementary mathematics teachers. Pre-service teachers were given five open ended linear and non-linear (quadratic) pattern problems which require them to find the general term of number patterns. Pre-service teachers' strategies to generalize and their use of mathematical models were analyzed. The analysis of data indicated that pre-service teachers described number pattern rules in relation to differences between terms and used visual models without a purpose. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Number patterns; mathematics teacher education; generalisation strategies